2010
DOI: 10.1897/ieam_2009-043.1
|View full text |Cite
|
Sign up to set email alerts
|

General recommendations for soil ecotoxicological tests suitable for the environmental risk assessment of genetically modified plants

Abstract: Before a genetically modified plant (GMP) can be placed on the market in the European Union (EU), an environmental risk assessment has to be conducted according to EU-Directive 2001/18/EC or Regulation (EC) No. 1829/2003 of the European Parliament and of the Council. However, no harmonized concept for ecotoxicological testing is available today that considers the characteristics of GMPs as a whole. In fact, to date, mainly ecotoxicological tests originally developed and standardized for pesticides are used for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 25 publications
0
20
0
Order By: Relevance
“…They must represent not only arable areas, but neighbouring receiving environments including wild habitats, where the GM crops may have a potential impact or could occur. There should be a representation of at least a) the main environmental compartments (terrestrial below-and aboveground, aquatic); b) functional groups such as predators, herbivores, saprophages, and symbionts; and c) different physiological, taxonomical groups, for instance, mainly arthropods but also oligochaetes, microbes and/or fungi (Hilbeck et al 2008a;Römbke et al 2009). …”
Section: Indicators and Sampling Methods (Tc1)mentioning
confidence: 99%
See 2 more Smart Citations
“…They must represent not only arable areas, but neighbouring receiving environments including wild habitats, where the GM crops may have a potential impact or could occur. There should be a representation of at least a) the main environmental compartments (terrestrial below-and aboveground, aquatic); b) functional groups such as predators, herbivores, saprophages, and symbionts; and c) different physiological, taxonomical groups, for instance, mainly arthropods but also oligochaetes, microbes and/or fungi (Hilbeck et al 2008a;Römbke et al 2009). …”
Section: Indicators and Sampling Methods (Tc1)mentioning
confidence: 99%
“…Depending on the selected indicator species, these methods may require modifications or new methods must be developed. Sub-lethal endpoints, such as reproduction, should be included as criteria since they can also give indications of possible long-term effects and are more sensitive than acute (lethal) harm (Römbke et al 2009). The methods identified have to be examined in practice, preferably in inter-laboratory comparison tests, and developed into a comprehensive testing protocol.…”
Section: Indicators and Sampling Methods (Tc1)mentioning
confidence: 99%
See 1 more Smart Citation
“…5 The five steps of current risk analysis procedures (hazard identification, exposure assessment, consequences assessment, risk characterization, mitigation options) were accepted as valid for GMOs, but methodologies and interpretations should be adapted to meet the specific features of living organisms and their interactions with the receiving environment [36][37][38][39]. Although Directive 2001/18/EC establishes a new framework for ERA prescribing the testing of the GMO as such (not only of the new genes and proteins) or the consideration of the receiving environment (not only some field trial locations as basis for an EU-wide approval), a review of the soil ecotoxicological tests presented in GMO dossiers concluded that they do not reflect the new legal requirements [40]. These authors, in line with Andow and Hilbeck and Snow et al, emphasise that it is crucial not to rely on standard test species only but to choose test species representative of the agro-ecological environments in which the GM plants will be grown [41,42].…”
Section: Different Reactions On the New Eu Biosafety Frameworkmentioning
confidence: 99%
“…In this context, numerous investigations have been carried out to assess the impact of current agricultural practices involving extensive monoculture, reduced crop rotation, use of fertilizers, herbicides and pesticides (Giller et al, 1997), and, currently, also the increasing use of genetically modified plants (GMP) (Bruinsma et al, 2003). Potential impact of GMP on soil microorganisms is often linked to specific properties of the transgenic trait, e.g., herbicide tolerant crops will be used together with a specific herbicide, insect resistant crops will possess different variant of Bacillus thuringensis (Bt) toxins (Römbke et al, 2010), while some of GMP also possess antibiotic resistance marker genes (Demanèche et al, 2008). A number of investigations have been carried out in order to determine the impact of GMP on soil microorganisms.…”
Section: Introductionmentioning
confidence: 99%